VARIASI PENGEMBANGAN MODEL LATIHAN PUKULAN (TSUKI) UNTUK KARATEKA PADA USIA 10-13 TAHUN - Indah Febriyani; Candra Kurniawan; Rian Jaya Sumantri; Dwi Priyono (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study seeks to create variations of the tsuki punch training model in karate for practitioners aged 10–13 years at the Ryuken Karate Club in Pesawaran Regency and to assess the enhancement of punching proficiency via frequency testing. The employed methodology is Research and Development (R&D) utilizing the Borg and Gall development model, which has ten stages. The research participants consisted of 30 karate practitioners. Expert validation results indicated that the created training model was viable, with evaluations of 91.42% from karate experts, 90% from linguists, and 85.7% from media experts, yielding an average score of 89.04%. The effectiveness test findings from punching frequency assessments indicated an enhancement in karateka punching proficiency. In the preliminary assessment, 4 individuals (13.33%) were classified as good, 19 individuals (63.33%) as sufficient, and 7 individuals (23.33%) as poor. Post-treatment, the good category rose to 10 individuals (33.33%), the sufficient group to 20 individuals (66.67%), and the poor category was eliminated. The implemented tsuki punch training model significantly enhanced the punch frequency of karate practitioners aged 10 to 13. The research culminates in a comprehensive guidebook detailing variations of training models, accompanied by illustrations and explanations to aid trainers in the training process.